Investigation of the Spectral Line Intensities of the ν9 Band of the Trans-Conformer of Ethylene; Russian Physics Journal; Vol. 63, iss. 3 - Zyatkova (Ziatkova) A. G. Anastasiya Georgievna (2020, 2020)
Title screen